Convergence justifications within political liberalism: A defence - Billingham, P (Springer, 2015)
According to political liberalism, laws must be justified to all citizens in order to be legitimate. Most political liberals have taken this to mean that laws must be justified by appeal to a specific class of ‘public reasons’, which all citizens can accept. In this paper I defend an alternative, convergence, model of public justification, according to which laws can be justified to different citizens by different reasons, including reasons grounded in their comprehensive doctrines. I consider three objections to such an account – that it undermines sincerity in public reason, that it underestimates the importance of shared values, and that it is insufficiently deliberative – and argue that convergence justifications are resilient to these objections. They should therefore be included within a theory of political liberalism, as a legitimate form of public justification. This has important implications for the obligations that political liberalism places upon citizens in their public deliberations and reason-giving, and might make the theory more attractive to some of its critics, particularly those sympathetic to religious belief.